Thermal Fluid Flow Transport Phenomenon in Unsteady Rotating Drum during Spin-Down Process - Shuichi Torii; Wen-Jei Yang (International Journal of Rotating Machinery)
Numerical analysis is performed on unsteady-state thermal fluid flow transport phenomena in a rotating drum heated at constant wall temperature during a spin-down process. Emphasis is placed on the effect of aspect ratio of the drum on the velocity and temperature fields. The governing equations are discretized by means of a finite-difference technique and numerically solved to determine the distributions of velocity vector and fluid temperature in the drum. It is disclosed from the study that (i) the formation of Ekman boundary layers on both sidewalls of the drum results in a pair of recirculating flows, and (ii) an attenuation of the flow velocity is affected by the aspect ratio of a drum. Results may be used to develop a method to achieve uniform mixing in an enclosed vessel.